Crystal structure and XANES investigation of petzite, Ag3AuTe2. Issue 2 (9th April 2019) - Hongu, Hidetomo; Yoshiasa, Akira; Nespolo, Massimo; Tobase, Tsubasa; Tokuda, Makoto; Sugiyama, Kazumasa
Abstract : A single‐crystal X‐ray diffraction and XANES investigation of the mineral petzite is reported. Abstract : Petzite, Ag3 AuTe2, crystallizes in the space group I 41 32, which is a Sohncke type of space group where chiral crystal structures can occur. The structure refinement of petzite reported long ago [Frueh (1959). Am. Mineral. 44, 693–701] did not provide any information about the absolute structure. A new single‐crystal X‐ray diffraction refinement has now been performed on a sample from Lake View Mine, Golden Mile, Kalgoorlie, Australia, which has resulted in a reliable absolute structure [a Flack parameter of 0.05 (3)], although this corresponds to the opposite enantiomorph reported previously. The minimum Te–Te distance is 3.767 (3) Å, slightly shorter than the van der Waals bonding distance, which suggests a weak interaction between the two chalcogens. XANES spectra near the Au and Te L III edges suggest that the chemical‐bonding character of Au in petzite is more metallic than in other gold minerals.